PENGARUH LKPD TERINTEGRASI PERMAINAN TRADISIONAL KARAPAN KALELES TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS 4 SDN PEJAGAN 1 - Kusuma, Eka Maya; Bagus Rahmad Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the use of LKPD integrated with karapan kaleles traditional games on the creative thinking ability of grade 4 students at SDN Pejagan 1. The method used in this study is quantitative with a Quasi Experimental Non-equivalent Control Group design with the entire population of grade 4 students. Purposive sample sampling technique. The number of samples in this study was 22 in the experimental class and 22 in the control class. The research results show that using integrated LKPD (Student Worksheet) with traditional games can influence students' creative thinking abilities, with a t-test hypothesis testing result of 0.041<0.05. This is because LKPD integrates traditional games that invite students to explore the environment and invite students to move